The effect of environmental costs and factors affecting environmental accounting on firm profitability of publicly-listed industrial companies in the Philippines - Acis, Kaycee Nicole E. (Animo Repository, 2021)
There are companies whose industry is greatly focused on using natural resources that create a larger contribution in the destruction of the environment. These industries would allocate costs to obtain or manufacture their product while also allocating costs to preserve the environment as regulated by environmental laws created by the government. The method to be adopted is the environmental accounting standards, which help translate socially and environmentally responsible behavior in monetary terms. The study aims to establish the effect of environmental accounting, and the factors affecting it, on the profitability of industrial companies that are publicly-listed in the Philippines from 2015-2019. The study will utilize Panel Data Regression to analyze the effect of environmental accounting, and the factors affecting it, on firm profitability. Environmental accounting was measured by the environmental costs incurred by the company. While the factors affecting Environmental Accounting are the Number of Board Members, Years Listed in the PSE, Independent Auditor Type, Firm Size, and Financial Leverage. On the other hand, Firm Profitability was measured using Return on Capital Employed, Net Profit Margin, Dividends per Share, and Earnings per Share. The findings presented that environmental costs and factors affecting environmental accounting had a significant effect on firm profitability represented by Return on Capital Employed. Meanwhile, environmental costs and factors affecting environmental accounting had no significant effect on firm profitability represented by Net Profit Margin, Dividend per Share, and Earnings per Share. Overall, the results presented that declaration of environmental costs may be greatly beneficial to a company’s firm profitability.